Climate change favours large seasonal loss of Arctic ozone - Gathen, Peter von der; Kivi, Rigel; Wohltmann, Ingo; Salawitch, Ross J.; Rex, Markus (Prof. Dr.) (Nature Communications, 2021)
Chemical loss of Arctic ozone due to anthropogenic halogens is driven by temperature, with more loss occurring during cold winters favourable for formation of polar stratospheric clouds (PSCs). We show that a positive, statistically significant rise in the local maxima of PSC formation potential (PFPLM) for cold winters is apparent in meteorological data collected over the past half century. Output from numerous General Circulation Models (GCMs) also exhibits positive trends in PFPLM over 1950 to 2100, with highest values occurring at end of century, for simulations driven by a large rise in the radiative forcing of climate from greenhouse gases (GHGs). We combine projections of stratospheric halogen loading and humidity with GCM-based forecasts of temperature to suggest that conditions favourable for large, seasonal loss of Arctic column O-3 could persist or even worsen until the end of this century, if future abundances of GHGs continue to steeply rise. Despite a ban on ozone depleting substances, ozone depletion during cold winters in the Arctic stratosphere has been increasing in recent decades. Here, the authors show conditions favourable for Arctic ozone depletion could worsen as a response of stratospheric temperature and water to continued release of greenhouse gases.